Analisis Faktor Yang Memengaruhi Pelaksanaan Vaksinasi Covid-19 pada Lansia di Kota Kendari - Nurnaningsih Nurnaningsih; Sartiah Yusran; Asnia Zainuddin (NHM PRESS, 2022)
In the implementation of vaccination, not all elderly groups can be vaccinated, these groups are comorbid groups and Covid-19 survivors. Preliminary studies conducted note that there is still a negative perception of the Covid-19 vaccine. The purpose of this study was to analyze the factors that influence the implementation of Covid-19 vaccination in the elderly in Kendari City. The data were analyzed using the chi square test analysis. The results showed that the knowledge of the elderly respondents in Kendari City, respondents who had good knowledge were 65 respondents (65.0%) while respondents with less knowledge were 35 respondents (35.0%). Respondents who have a good attitude there are 60 respondents (60.0%) while respondents with less attitude are 40 respondents (40.0%). Respondents who received support in the good category were 67 people (67.0%) while respondents with less family support were 33 people (33.0%). Respondents who assessed the waiting time for vaccination services in the good category were 56 people (56.0%) while the respondents who rated the waiting time for vaccination services in the poor category were 44 people (44.0%). There is a relationship between the implementation of vaccines in the elderly with knowledge (P-value < 0.000), attitude (P-value < 0.000), family support (P-value < 0.000), waiting time for services (P-value < 0.000). The conclusion in this study is that there is a significant influence between knowledge, family support and affordability of covid-19 vaccination in the elderly in Kendari City.